Total Phenolic Content and Antibacterial Activity of Nut Grass (Cyperus rotundus L.) Extract - Masfria; Metri Permata, Yade (Indonesian Journal of Pharmaceutical and Clinical Research, 2018)
Abstract. The objectives of this research was to study the macroscopic, the microscopic and phytochemicals characterization of raw materials, total polyphenol content and the antibacterial activity of nut grass extracts (Cyperus rotundus L.) against Shigella dysenteriae, Salmonella typhimurium, Staphylococcus epidermidis, and Pseudomonas aeroginosa. The macroscopic and the microscopic characterization of raw materials were done with the determination of the water contents, the water soluble contents, the ethanol soluble contents, total ash and acid soluble ash. The extract was prepared by percolation using n-hexane, ethanol, and ethyl acetate as solvents. Phytochemical screening was done on the raw materials as well as n-hexane, ethyl acetate, and ethanol extracts. Total phenol contents were tested with the Folin-Ciocalteu reagent method. The antibacterial activity test was done by measuring the diameter of the inhibition zones using the diffusion agar method. The results showed that raw material retrieved 7.33% water content, 21.85% water soluble contents, 7.9% ethanol soluble contents, 1.53% total ash, and 0.67% total insoluble-acid ash. The phytochemical study showed that the nut grass contains various secondary metabolites including flavonoids, glycosides, saponins, anthraquinone glycosides, and steroid/triterpenoids. The total polyphenol contents of ethanol extracts were expressed as catechin equivalents 1.1616 mg/g extract. All of the nut grass extract showed antibacterial activity. Ethyl acetate extract of nut grass indicated the highest antibacterial activity against Shigella dysenteriae, Salmonella typhimurium, and Pseudomonas aeroginosa. Ethanol extract was only effective against Staphylococcus epidermidis. Keywords: Antibacterial Activity, Bacteria, Cyperus Rotundus L Extracts, Phenolic